Sharia investment Challenges and Growth for Sustainable and Inclusive Financial Equality in Digital Innovation - Kenneh, Mohammed (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2024)
The article explores how Islamic finance aligns with sustainability goals converge and shows how Sharia finance can help promote a more equitable and environmentally friendly world. The research method used is a Systematic Literature Review with a descriptive approach. The (LSR) approach is a mixture of collecting relevant and legitimate academic literature from diverse sources. The finding of the research shows that various sustainability objectives are aligned with the basic principles of risk sharing, Socially Responsible Investment, Prohibition of Harmful Investments, Prohibition of Riba (Interest), and Avoidance of Gharar (Uncertainty). Infrastructure developments and renewable energy projects can be promoted by instruments like Islamic Bonds (Sukuk), Sharia-Compliant Funds, Islamic Loans and Islamic Insurance that satisfy Sharia law. These efforts are enhanced through innovations that allow mobile banking services or microfinancing solutions, reaching out even to marginalized groups by Islamic principles. Despite all these, the finding also shows that there are some challenges face by Islamic banking in various countries. The mean challenges faces are: Regulatory challenges, Interpretation of sharia law, Market Competitiveness, and Lack of Awareness. It is essential to have sharia interpretations and sound regulatory frameworks to enhance transparency and prevent malpractices. Furthermore, improving literacy and increasing access to technology is essential to help narrow the gap and ensure equal participation in financial sectors for inclusiveness. In this era of technological advancements, by addressing these challenges while leveraging the capabilities of instruments compliant with Shariah principles, Islamic investment products may drive sustainable inclusive finance.